Positive Classroom Design through Social-Emotional Learning: Building a Community of Learners - Sorbet, Stefanie R; Notar, Charles E (American Journal of Education and Learning, 2022)
There is a direct relationship between meeting the needs of our students through providing a positive learning environment that is rich in social and emotional learning and building a community of learners who want to be engaged in their learning. Students who participate in social and emotional learning in the classroom are able to practice self-control, self-management, responsible decision-making, relationship skills, and social awareness (Casel, 2020). Social and emotional learning activities and lessons help teachers to meet the basic needs of their students in order for them to thrive in their learning environment. When basic needs are met and social-emotional learning competencies are achieved, students feel a sense of community in their classroom. When students feel a part of a positive environment, behavior decreases, and engagement increases. The article is based on a review of the literature and the personal experiences of one of the authors.